PENGETAHUAN, SIKAP DAN TINDAKAN IBU-IBU RUMAH TANGGA PADA SAAT PRA BENCANA WABAH PENYAKIT DEMAM BERDARAH DENGUE DI KOTA BANDA ACEH - Nelly Susanty; Teuku Tahlil; Nizam Ismail (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2017)
This research aimed to improve the housewives’ level of knowledge, attitude and action on the pre-epidemic of dengue fever and to know the relationship and the influence of knowledge and attitude toward the action in preventing the dengue fever on the pre-epidemic of dengue fever in Banda Aceh Municipality. The research design used quantitative approach and it was strengthened by the qualitative approach. The sample of this research is 99 respondents which are chosen using the purposive sample. The technique of collecting data was conducted using questionnaire and semi-structure interview. The data were analyzed using univariate, bivariate, and content analysis. The research result showed the housewives’ knowledge, attitude, and action the pre-epidemic of dengue fever in Banda Aceh Municipality were categorized in the low level. It has relation and knowledge influence, behavior toward the housewives’ action in preventing dengue fever through both Drain Shut Bury action program and Drain Shut Bury Plus Action Program on the pre-epidemic of dengue fever in Banda Aceh Municipality. For the housewives, it is expected that they can improve the understanding about the self-warning system toward the danger of dengue fever by actively seeking the information to both from the media and the health staff